Additions to the leafhopper subgenus Pediopsoides (Pediopsoides) Matsumura, 1912 (Hemiptera: Cicadellidae: Macropsinae) from Southern China - Li, Hu; Li, Zi-Zhong (Zootaxa, 2016)
Three new species of the leafhopper subgenus Pediopsoides (Pediopsoides) Matsumura, 1912, P. (P.) alba Li, Dai & Li sp. nov. from Yunnan Province, Southwestern China, P. (P.) amplificata Li, Dai & Li sp. nov. and P. (P.) longiapophysis Li, Dai & Li sp. nov. from Guangdong Province, Southern China, are described and illustrated. A key and an updated checklist with distribution to the Pediopsoides (Pediopsoides) species along with geographical distribution maps of the new species are given.